Pengaruh Terpaan Iklan Televisi, Instagram Series, dan Celebrity Endorser Terhadap Keputusan Memilih Partai Solidaritas Indonesia pada Pemilih Pemula - Rohedy Ayucandra; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This study aims to determine the effect of television advertisement, Instagram series, and celebrity endorsers exposure toward the decision to choose the Indonesian Solidarity Party in first voters. In determining the hypothesis to be used, this study uses a cognitive response approach. To determine the sample, this study used a nonprobability sampling technique by accidental sampling. The number of samples studied amounted to 60 people with characteristics residing in the city of Semarang, aged 17-21 years, and have seen television commercials, Instagram series, and celebrity endorsers of the Indonesian Solidarity Party. Analysis of the data used in this research is Multiple Linear Regression Analysis. Before conducting a hypothesis test, the classical assumption test is performed first. Hypothesis test results indicate that there is no influence of exposure to advertising on television, Instagram series, and celebrity endorser together on the decision to choose the Indonesian Solidarity Party in the novice voter. However, different results were found that there was an influence of the Instagram series and celebrity endorser on the decision to choose the Indonesian Solidarity Party when a simple linear regression test was performed.